Effects of the Activity-based Learning Enhancing Program on Knowledge and Practices of Wounds First Aid Among Student Leaders - Jaikla, Navarut; Tuanrat, Wilawan; Aungwattana, Sivaporn (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental research aims to evaluate the effects of an activity-based learning enhancing program on knowledge and practices of basic wound first aid among student leaders. The sample consisted of 36 primary school students (Grades 4–6) serving as class presidents, vice-presidents, or selected as potential student leaders. Participants were randomly assigned to experimental and control groups, with 18 students in each group. The research instruments included: (1) an activity-based learning enhancing program on wound first aid for student leaders, developed based on the activity-based learning (ABL) framework, over a 4-week period; (2) and a basic wound first aid manual. The data collection tools comprised: (1) a knowledge questionnaire on basic wound first aid for student leaders, which achieving a content validity index of 0.94 and reliability (KR-20) = 0.73, and (2) an observation form to assess basic wound first aid practices for student leaders. Inter-rater reliability yielded an Item-Objective Congruence (IOC) index ranging from 0.815 to 0.984 with a 95% confidence level. The data were analyzed by using the paired sample t-test, independent t-test and Fisher’s exact Test The results revealed that the experimental group showed significantly higher post-intervention scores in both knowledge and practical skills compared to their pre-intervention scores and to the control group (p < .001). These findings suggest that the Activity-based Learning enhancing Program effectively enhances student leaders’ competencies in basic wound first aid and can serve as a valuable strategy for student health leadership development in schools.